Sobre uma classe de equações elípticas envolvendo crescimento exponencial em ℝ2 - Guimarães, Wanderson Rodrigo (2013)
In this work, we will study the existence and multiplicity of weak solutions for a class of nonhomogeneous elliptic problems involving exponential growth Trudinger-Moser type in R2. For this, we will use the Ekeland s Variational Principle and the Mountain Pass Theorem without the Palais-Smale condition in combination with a version of the Trudinger-Moser inequality.